Development of realistic mathematics education-based worksheets to facilitate mathematical connection abilities on pythagorean theorem material - Nadeak, Devi Irawaty; Murni, Atma; Heleni, Susda (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aimed to develop a student worksheet on the Pythagorean Theorem utilizing the Realistic Mathematics Education (RME) approach, designed to meet validity and practicality standards to enhance the mathematical connection abilities of 8th-grade students. The research adopted the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. To ensure the validity of the student worksheet, three experts conducted a comprehensive validation process. Feasibility data were collected through trials involving 8th-grade students. The validation results indicated a score of 90.77%, categorized as "very valid." Small group trials yielded a practicality score of 89.98%, categorized as "very practical." Furthermore, large-scale trials demonstrated an average score of 89.29%, also categorized as "very practical." These findings highlight the effectiveness of the RME approach in facilitating students' mathematical connection abilities through the Pythagorean Theorem material. The developed student worksheet was proven to be valid, practical, and highly beneficial for supporting the development of mathematical connections among 8th-grade students.